Increasing the production capacity of copper drawing machine in the cable industry using SMED method: A case study in Indonesia - Lilik Setyawan (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
Indonesian Government has electricity program of 35,000 Megawatt. To make this program successful, all cable companies begin to implement strategies to satisfy these needs. Increasing the production capacity is the main program implemented by cable companies in Indonesia. One of the cables companies has production output on copper drawing machine of 11 unit of bobbins per shift with the production process cycle time of 32.32 minutes per bobbin. To improve production capacity, improvements need to be performed to reduce the cycle time of the production process. This research was conducted by applying fishbone and Pareto analysis resulting in three main research problems. SMED methodology was implemented in this research by separating two activities, namely internal setup and external setup, then turning the internal setup to external setup in order to reduce the overall processing duration. From the three main research problems, it results in processing duration reduction from 32.32 minutes to 23.18 minutes or a reduction of 28.28 percent. This reduction can improve the production capacity from 11 unit of bobbins to 16 unit of bobbins per shift or 360 unit of bobbins monthly or increasing the production capacity of 45.45 percent. This SMED program is very suitable for similar companies in cabling field and having old machines so that they do not need to invest by purchasing a new machine.